Hydrophobic modification of bacterial cellulose using oxygen plasma treatment and chemical vapor deposition - Leal, S. (2020)
A new strategy for the surface modification of bacterial cellulose (BC) through the combination of oxygen plasma deposition and silanization with trichloromethyl silane (TCMS) is described. The combined use of the two techniques modifies both the surface roughness and energy and therefore maximizes the obtained hydrophobic effect. These modified membranes were characterized by Scanning Electron Microscopy (SEM), water contact angle measurements, Fourier-transform infrared spectroscopy (FTIR-ATR) and X-ray photoelectron spectroscopy (XPS), and its cytotoxic potential was investigated using both indirect and direct contact in vitro studies. The obtained results suggest an effective conjugation of TCMS to the surface of BC, leading to a highly hydrophobic surface, with a water contact angle of approximately 130º. It is also demonstrated that this is a stable and durable surface modification strategy, since BC remained hydrophobic even after 6 months, in dry conditions or after being submerged in distilled water for about a month. Importantly, this surface modification revealed no short-term cytotoxic effects on L929 and hDNFs cells. Altogether, these data indicate the successful development of a surface modification method that can be applied to BC, enabling the production of a biodegradable and hydrophobic platform that can be applied to different areas of research and industry.